2011
DOI: 10.4067/s0034-98872011000700008
|View full text |Cite
|
Sign up to set email alerts
|

Un estudio de reclamos hospitalarios: el rol de la relación médico-paciente

Abstract: A study of hospital complaints and the role of the doctor-patient communication Background: Medical practice in Chile has changed dramatically over the last few years. Patients have raised their expectations and there is a growing number of complaints, and malpractice lawsuits. The doctor-patient relationship plays a fundamental role in patient satisfaction and has also been identifi ed as an issue in most medical lawsuits. Aim: To analyze the importance of doctor-patient communication in the complaints receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 31 publications
0
2
0
2
Order By: Relevance
“…However, although the hierarchical medical policy has improved workloads, healthcare workers continue to report severe job stress. Challenge stress is still high among healthcare workers in all types of hospitals, and especially in tertiary hospitals because the number of patients and their expectations for quality of care are rising [ 30 , 31 ]. Moreover, frequent incidents of medical violence and the large variety of work tasks increase challenge stress [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, although the hierarchical medical policy has improved workloads, healthcare workers continue to report severe job stress. Challenge stress is still high among healthcare workers in all types of hospitals, and especially in tertiary hospitals because the number of patients and their expectations for quality of care are rising [ 30 , 31 ]. Moreover, frequent incidents of medical violence and the large variety of work tasks increase challenge stress [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finalmente, dado que, en el contexto social actual, el respeto por el otro se sitúa como uno de los principales valores a defender y procurar, existe un gran espacio para reducir las tasas de reclamos debido a lo que hemos llamado falla en el trato y comunicación con el médico y que en otras publicaciones son englobadas como menoscabo en el "trato digno" 6,[12][13][14] . Debemos reforzar la formación integral de los médicos, con el fin de que las situaciones de conflicto por asuntos relativos a las relaciones humanas, que se dan en el binomio paciente-médico, se minimicen y eventualmente, desaparezcan 15 .…”
Section: Discussionunclassified
“…La tasa de reclamos por atenciones efectuadas, su naturaleza y la forma de resolverlos habitualmente queda en los registros internos de los centros. En Chile, de experiencia de prestadores privados, sólo conocemos la publicada por Moore et al 6 en el Hospital Clínico de la Pontificia Universidad Católica de Chile, el año 2011. El objetivo del presente trabajo es analizar las causas y manejo de los reclamos en un centro privado de salud, también universitario, que presentaron pacientes o sus familiares, de acuerdo al derecho de las personas, consagrado por la referida Ley 20.584.…”
unclassified
“…Research has shown that effective patient-physician communication can improve health outcomes [42–45]. On the other hand, a lack of physician-patient communication also generates more recurrent medical litigations [4649]. The event-based model is considered ineffective [37, 41, 50, 51], additionally contributing to inappropriateness, as only written information is provided and this does not necessarily imply that patients are truly informed about the risks and benefits of the examination and potential alternatives [52, 53].…”
Section: Informed Consentmentioning
confidence: 99%